Mineral Water Bottle Waste as a Project to Strengthen the Pancasila Student Profile in 21st Century Paradigm-Based Learning - Sakman, Sakman; Hadjranul Fatah, Abdul; Hayati, Siti (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aimed to describe the development of students' character in the dimensions of Loyalty, Piety to God Almighty, Mutual Cooperation, Independence, and Critical Thinking. This study used a qualitative method involving 31 students of class X.A at SMA Negeri 2 Muara Teweh. Data were collected through observations, interviews, and documentation. Observational data tracked character development, while interview data gathered insights into room comfort from students. Data analysis included presentation and verification of the data. The results showed that based on the assessment rubric, 38.70% of students were at the “starting to develop” stage, 48.38% were at the “developing” stage, and 12.90% were in the “developing as expected (skilled)” category. Among the 11 students interviewed, 32.25% reported the room was “somewhat warm,” 41.93% “quite cool,” and 25.80% “cool.” These findings indicate that awareness of waste utilisation and environmentally friendly character development still needs to be improved. Novelty: The novelty of this study lies in the integration of improving classroom air quality with character building that aligns with the six dimensions of the Pancasila Student Profile: Faith, Piety to God Almighty, Mutual Cooperation, Independence, and Critical Thinking, which adds a green environmental dimension to this educational initiative.